2022
DOI: 10.1029/2021jd036053
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Urbanization and Irrigation on Summer Climate in the Huang‐Huai‐Hai Plain, China

Abstract: Anthropogenic forcing, including greenhouse gas (GHGs) and aerosols, regional land use, and land management changes (e.g., irrigation) have all affected the observed regional climate changes (IPCC AR6, 2021). Biophysical effects of regional land changes that redistribute the energy and water vapor between the land and atmosphere further influence the regional climate (Shukla et al., 2019). Currently, much attention has been paid to GHGs, but only focusing on the biogeochemical feedback (while ignoring the biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…The terrain of the study area is relatively flat, but micro-terrain features such as the northern mountainous region and the southern hills affect the formation, intensity, and spatial-temporal distribution of extreme rainfall to a certain degree by influencing atmospheric stability, wind fields, and water vapor transport, among other factors [90]. Mountains can affect the generation of extreme precipitation by lifting or blocking low-level airflow and inducing substantial rain when unstable airflow impacts the terrain [91,92]. Meanwhile, the terrain affects atmospheric water vapor transport, and upward airflow can cause convective precipitation, enhancing precipitation intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The terrain of the study area is relatively flat, but micro-terrain features such as the northern mountainous region and the southern hills affect the formation, intensity, and spatial-temporal distribution of extreme rainfall to a certain degree by influencing atmospheric stability, wind fields, and water vapor transport, among other factors [90]. Mountains can affect the generation of extreme precipitation by lifting or blocking low-level airflow and inducing substantial rain when unstable airflow impacts the terrain [91,92]. Meanwhile, the terrain affects atmospheric water vapor transport, and upward airflow can cause convective precipitation, enhancing precipitation intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al. (2022) explored the interplay between urbanization and irrigation on summer climate in the NCP based on three regional climate model simulations with/without urbanization or irrigation and found that the cooling effect of irrigation exceeded the warming effect of urbanization. However, these studies used the observed vegetation data to update the land surface vegetation characteristics of the regional climate model, neglecting irrigation greening effect.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of irrigated area makes the NCP the largest irrigated area in China (Kang & Eltahir, 2019). Extensive studies have attempted to investigate the irrigation climatic effects over the NCP using regional climate model simulations and led to considerable achievements (e.g., Cui et al., 2022; Wu et al., 2018; Yang et al., 2016). For instance, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations